Ultrathin Ni-MOF Nanobelts-Derived Composite for High Sensitive Detection of Nitrite - Meng, Xiangren; Xiao, Xiao; Pang, Huan (Frontiers in Chemistry, 2020)
In this paper, the Ni/NiO ultrathin nanobelts were successively synthesized by a facile in suit conversion process using pre-synthesized Ni-based metal-organic frameworks (MOFs) nanobelts as parent materials to detect the nitrite (NaNO2). The synthesized Ni/NiO composites have the advantages in structure, as follows: (I) Interleaved 3D reticulated structure has strong mechanical stability; (II) Ultrathin nanobelt structures allow more active sites to be exposed and make the transfer of charge faster; (III) A large number of ultrafine Ni nanoparticles decorate the building blocks of the NiO nanobelt and enhance the electrical conductivity. Ni/NiO/GCE has an obvious oxidation peak at 0.78 V, when the concentration is between 0.5 and 1000 μM, the oxidation peak current of NaNO2 is linearly related to the concentration, and the sensitivity is 1.5319 μA mM-1 cm-2 (S/N = 3). Moreover, the experimental results also concluded that the Ni/NiO ultrathin nanobelts not only indicated wonderful reproducibility in the determination of NaNO2 in the pickled pork samples, but also could be well recovered and keep stable for a long time.